Two factors predicting the academic success of high school students: justice in classroom management and school engagement - Özgenel, Mustafa; Bozkurt, Büşra Nur; Özgenel, Mustafa (Pegem Akademi Yayıncılık, 2019)
The purpose of this study was to determine the predictive value of classroom justice perceptions and school engagement for academic success of high school students. The sample of the study consisted of 650 high school students studying in Istanbul City in the 2018-2019 academic year. The study was designed as a correlational survey study. The data were collected by classroom justice perception of students and the school engagement scales. The data were analyzed by independent t-test, one-way analysis of variance (ANOVA), correlation and regression analyses. The results suggest that there is a significant difference between high school students’ perceptions of justice in classroom management and their school engagement levels according to their gender, class levels and the types of schools they were educated. Besides, positive and low correlation was found between school engagement levels with distributive and awarding justice. It was concluded that the teachers should be fair in evaluating the students while ensuring fair classroom conduct.

Bu çalışmanın amacı, lise öğrencilerinin sınıf yönetimindeki adalet algıları ile okula bağlılık düzeyleri ve akademik başarıları arasındaki ilişkileri ve lise öğrencilerinin sınıf içi adalet algılarının ve okula bağlılıklarının birlikte, akademik başarılarının bir yordayıcısı olup olmadığını belirlemektir. Araştırmanın örneklemini 2018-2019 eğitim-öğretim yılında İstanbul İlinde eğitim gören 650 lise öğrencisi oluşturmaktadır. Araştırma modeli olarak ilişkisel tarama modeli kullanılmıştır. Veriler ‘‘Sınıf Yönetiminde Adalet Algısı Ölçeği’’ ve ‘‘Okula Bağlılık Ölçeği’’ yardımıyla toplanmıştır. Veriler bağımsız gruplar t-testi, tek yönlü varyans analizi (ANOVA), korelâsyon ve regresyon analizleri ile çözümlenmiştir. Araştırma sonucuna göre lise öğrencilerinin sınıf yönetimindeki adalet algıları ve okula bağlılık düzeylerinde cinsiyetlerine, sınıf seviyelerine ve eğitim gördükleri okul türlerine göre anlamlı bir farklılık bulunmuştur. Öğretmenler, öğrenciler için adil bir sınıf yönetimi sağlarken yaptıkları değerlendirmelerde adil olmaları gerektiği sonucuna varıldı.
Lise öğrencilerinin akademik başarılarını yordayan iki faktör: sınıf yönetiminde adalet ve okula bağlılık
Keywords: Classroom management; Justice; School engagement; Academic success; Sınıf yönetimi; Adalet; Okula bağlılık; Akademik başarı